The study on relationship between macroeconomics variables toward non-performing loan on banking sector in Malaysia / Mohd Nur Farhan Mohmad Khalid - Mohmad Khalid, Mohd Nur Farhan (2015)
This paper uses time series data methods to examine the determinants of nonperforming loans (NPLs) on banking sector in Malaysia with the macroeconomic variables. The study is motivated by the hypothesis that macroeconomic variables have an effect on NPLs. All these macroeconomic variables consist of Unemployment Rate, Gross Domestic Product, and Inflation. Moreover, the NPLs data, and selected macroeconomic variables will be gain from the Bank Negara Malaysia, from year 2000 until 2013, quarterly.